2002
DOI: 10.1021/la010884f
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation Study of Concentration Effects and Scattering Functions for Polyelectrolyte Wormlike Micelles

Abstract: We present an extensive Monte Carlo study on systems of many semiflexible chains with excluded volume and electrostatic interactions within the Debye−Hückel approximation. The model is tuned to mimic charged wormlike micelles in solution under different conditions. Simulations have been performed at different ionic strengths of added salt, charge densities, chain lengths, and volume fractions (η), covering the dilute to concentrated regime. The simple model used is able to reproduce the structural peak of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…We observe exactly the same behaviour as reported for polymer-electrolyte and salt free (or lowionic strength) wormlike micelle solutions (Sommer et al, 2002). Cannavacciuolo et al (2002) carried out a Monte Carlo simulation on systems consisting of many charged wormlike micelles with excluded volume and electrostatic interactions and concluded that the scattering function becomes almost identical with that of uncharged system when the ionic strength is more than 0.1 mol l À1 . This is because the electrostatic screening due to added salt is large enough to reduce repulsion between charged micelles.…”
Section: Structure Factorssupporting
confidence: 54%
See 1 more Smart Citation
“…We observe exactly the same behaviour as reported for polymer-electrolyte and salt free (or lowionic strength) wormlike micelle solutions (Sommer et al, 2002). Cannavacciuolo et al (2002) carried out a Monte Carlo simulation on systems consisting of many charged wormlike micelles with excluded volume and electrostatic interactions and concluded that the scattering function becomes almost identical with that of uncharged system when the ionic strength is more than 0.1 mol l À1 . This is because the electrostatic screening due to added salt is large enough to reduce repulsion between charged micelles.…”
Section: Structure Factorssupporting
confidence: 54%
“…On the other hand, for randomly oriented rodlike or wormlike micelles, the calculation becomes difficult. Recently, Cannavacciuolo et al (2002) presented an extensive Monte Carlo study on charged wormlike micelles to calculate S(q). To obtain P(q) from the observed data, I(q)/C D was extrapolated to the limit C D !…”
Section: Theoretical Background and Saxs Data Analysismentioning
confidence: 99%
“…We note that if all monomers of DNA were charged, one obtains B 29 and the range of these experimentally realizable B values are similar to the ones considered in this study. Another system with a comparably high linear charge densities is solution of charged worm-like micelles [47][48][49] . We hope that experimentalists find it interesting to check the existence of different collapse regimes for different counterion valencies and sizes.…”
Section: Discussionmentioning
confidence: 99%
“…to the measured SAXS data for three concentrations c j for each q value q i ; P i , R int and a are fit parameters. The approach is similar to a classical Zimm analysis, except that it is expected to be applicable at higher concentrations in the full SAXS q range, since it has a more general form that can reproduce the behaviour found by PRISM theory and simulations for more strongly interacting systems 25. The fit to the data was performed using a standard nonlinear least‐squares method, and the standard error on the data extrapolated to zero concentration P i is directly obtained from the least‐squares analysis as the errors on the fit parameters.…”
Section: Methodsmentioning
confidence: 99%